Innovation for inclusive development in Southeast Asia: the roles of regional coordination mechanisms. Issue 4 (7th August 2016) - Ng, Boon-Kwee; Kanagasundram, Thiruchelvam; Wong, Chan-Yuan; Chandran, V.G.R.
Abstract: In the past, studies on inclusive development involve mainly the perspective of equitable distribution of economic and societal outputs. This study, however, takes a different approach and analyses the potential roles of regional coordination mechanisms (RCMs), specifically universities and research council's networks within Southeast Asia, in disseminating the innovation-related activities for inclusive development or Innovation for Inclusive Development (IID). The literature on innovation intermediaries within the realm of innovation systems studies was used to establish the framework of the study. The findings indicate that RCMs have a huge potential role to play. However, due to a number of reasons, including lack of funding support, lack of attention and commitment to IID, weak engagement with industry and non-governmental organisations, the implementation of the IID activities was rather poor. As a whole, the study argues that current approaches are not well positioned and it is fragmented preventing the effective use of RCMs despite their potentials for IID efforts. The study attributes this to the systemic failures in the regional coordinating systems. In enhancing the role of RCMs in IID, this study recommends the promotion of IID platform, the leveraging of non-government organisations and industry as well as energising the Southeast Asia engagement in promoting IID.